A Analisis Spasial Daerah Rawan Longsor Di Kecamatan Latambaga Kabupaten Kolaka - Iskandar, Ahmad; Kamur, Sudarwin; Kharisma, Gaby Nanda; Awal, Samsi; Hanusi; Hasan, Radif (Mataram University, 2024)
Kolaka Regency is an area with topographic conditions dominated by hills and steep slopes and has high rainfall intensity. Latambaga is one of the districts in Kolaka Regency which is prone to landslides. Therefore, this research aims to spatially analyze areas prone to landslides in Latambaga District, Kolaka Regency. This type of research is descriptive quantitative using data on slope slope, land use, rainfall and soil type. These data were analyzed using weighting and scoring. The research results of landslide hazard maps were created using GIS with the ArcGIS 10.3 software application through an overlay stage process. Based on the research results, it shows that the area is not prone to landslides covering an area of 2,519.83 Ha or 8.95%, the area is slightly prone to landslides covering an area of 12,775.49 Ha or 45.38%, the area is quite prone to landslides covering an area of 4,621.18 Ha or 16.41%, landslide prone areas are 3,874.94 Ha or 13.76% and very prone areas are 4,246.24 Ha or 15.08%.